Changes in functional status and inflammation profile in patients with chronic obstructive pulmonary disease during therapy with tiotropium - I. N. Trofimenko; B. A. Chernyak (Медицинский совет, 2015)
The article tells about the results of evaluating the effects of tiotropium on the level of bronchial hyperresponsiveness (BHR) and comparing its clinical efficacy in patients with chronic obstructive pulmonary disease (COPD) depending on the level of bronchial reactivity. Ttreatment with tiotropium was associated with a decrease in BHR (p